Pengembangan E-Modul Berbasis Project-Based Learning Pada Mata Pelajaran Instalasi Motor Listrik - kurnia, Hendra; Myori, Dwiprima Elvanny (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
One effort to achieve learning objectives is the use of Electric Motor Installation teaching materials. However, due to the limited number of printed materials, not all students have access to books that can serve as learning resources. To address this issue, an Electric Motor Installation e-module was developed using a Project-Based Learning model. This research aims to develop an Electric Motor Installation e-module based on Project-Based Learning that is both valid and practical. The type of research conducted is Research and Development (R&D), using the 4-D model, which consists of four stages: Define, Design, Develop, and Disseminate. However, this study was conducted up to the third stage, Develop. The research employed instruments including a validity test questionnaire and a practicality questionnaire. The data obtained were analyzed using the Moment Kappa (k) coefficient to determine the validity and practicality of the e-module. The results of the study show that the developed e-module achieved a validity score of 0.88, categorized as very valid. The practicality test results from teachers indicated a score of 0.91, categorized as very practical, while the student practicality test yielded a score of 0.86, also categorized as very practical. In conclusion, the Electric Motor Installation e-module based on the Project-Based Learning model is valid and practical.